Potable water : emerging global problems and solutions - Grady, Caitlin A.; Younos, Tamim (The Handbook of Environmental Chemistry, 2014)
This volume presents a unique and comprehensive glimpse of current and emerging issues of concern related to potable water. The themes discussed include: (1) historical perspective of the evolution of drinking water science and technology and drinking water standards and regulations; (2) emerging contaminants, water distribution problems and energy demand for water treatment and transportation; and (3) using alternative water sources and methods of water treatment and distribution that could resolve current and emerging global potable problems. This volume will serve as a valuable resource for researchers and environmental engineering students interested in global potable water sustainability and a guide to experts affiliated with international agencies working toward providing safe water to global communities.